Electrospun Nanofibers for New Generation Flexible Energy Storage. Issue 4 (23rd December 2020) - Yan, Yonghui; Liu, Xiangye; Yan, Jing; Guan, Cao; Wang, John
Abstract : As one of the essential components for flexible electronics, flexible electrochemical energy storage (EES) has garnered extensive interests at all levels of materials, devices, and systems. The successful implementation of high‐performance flexible EES devices relies on exploring of suitable electrode/electrolyte materials that have both superior electrochemical and mechanical properties. For this function, one‐dimensional electrospun nanofibers have emerged as a class of promising building blocks for the key components of flexible EES devices. In this overview, the fundamental principles and technical advances of electrospinning are examined, for both their successes and challenges in controllable fabrication of nanofibers with the desirable chemical compositions, micro/meso‐/nanostructures, and therefore resultant properties. The advances in applications of electrospun nanofibers for various key flexible EES devices are critically looked into, including those in supercapacitors, metal‐ion batteries, and metal‐air batteries. The existing challenges and prospects of these electrospun nanofiber‐based flexible EES are discussed, aiming to inspire continued efforts in developing the optimal high‐performance and low cost flexible EES devices for long‐awaited practical applications. Abstract : The advantages of versatile electrospun nanofibers as building blocks for flexible electrochemical energy storage devices are reviewed. The development of electrospun fiber‐based flexible energy storage devices, including supercapacitors, metal‐ion batteries, and metal‐air batteries, is discussed, as well as their future prospects in both academia and commercial fields.